2022
DOI: 10.21203/rs.3.rs-1634970/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is sentinel lymph node biopsy without frozen section in early stage breast cancer sufficient in accordance with ACOSOG-Z0011? A retrospective review from King Chulalongkorn Memorial Hospital.

Abstract: Background: In 2021, increased implementation of the usage of permanent section (PS) without intraoperative frozen section (FS) for sentinel lymph node biopsy (SLNB) were evident worldwide. This pilot study conducted in Thailand will determine the re-operation rate in SLNB without FS technique. Method: we retrospectively reviewed 239 cases of SLNB without FS in King Chulalongkorn Memorial Hospital from April 2016 to April 2021. These patients were diagnosed with primary invasive breast cancer with clinical nod… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Additional iFS would not alter any standard of care in patients who fulfill the ACOSOG classification. 28 An Iranian study reinforced that low tumor burdens were detected from FS in early-stage breast cancer patients. 29 From a total of 214 cases analyzed in this 6-year retrospective review, 5 cases were found with more than two metastatic nodes which was an indication for further ALND in accordance with the Z0011 trial.…”
mentioning
confidence: 95%
“…Additional iFS would not alter any standard of care in patients who fulfill the ACOSOG classification. 28 An Iranian study reinforced that low tumor burdens were detected from FS in early-stage breast cancer patients. 29 From a total of 214 cases analyzed in this 6-year retrospective review, 5 cases were found with more than two metastatic nodes which was an indication for further ALND in accordance with the Z0011 trial.…”
mentioning
confidence: 95%